Cognitive Profile in Ultra High Risk for Psychosis and Schizophrenia: A Comparison Using Coordinated Norms - Anda, Liss; Brønnick, Kolbjørn K.; Johannessen, Jan Olav; Joa, Inge; Kroken, Rune A.; Johnsen, Erik; Rettenbacher, Maria; Fathian, Farivar; Løberg, Else-Marie (Frontiers in Psychiatry, 2019)
Background: Cognitive impairment is a core aspect of schizophrenia but also commonly observed in help seeking youth at ultra-high risk for psychosis (UHR), with potential implications for prognosis and individualised treatment. However, there is no consensus on the cognitive profile in the UHR state, partly due to lack of valid comparisons of performance in established schizophrenia and UHR. Objectives: To compare the cognitive functioning and profile of UHR subjects to a group with schizophrenia, using coordinated norms based on healthy controls reflecting the younger UHR age spectrum. Methods: Participants for UHR (n=51) and schizophrenia groups (n=48) were included from the Prevention of Psychosis (POP) and Bergen Psychosis 2 (BP2) projects. All subjects completed a comprehensive neurocognitive test battery aiming to measure processing speed, executive functioning, verbal and spatial ability. Cognitive functioning was compared between groups based on coordinated norms using z-scores derived by regression modelling from an age matched healthy control group (n=61). Results: UHR subjects showed significantly impaired processing speed (p<.001), executive functioning (p=.037) and verbal ability (p=.004) as compared to the control group. Spatial abilities appeared unimpaired. UHR subjects significantly outperformed the schizophrenia group for processing speed (p=.015). Conclusion: Cognitive performance is impaired in UHR subjects and should be monitored when a person is deemed at high risk of psychotic illness. Spatial skills, as measured by tests using physical objects, appear less affected than other domains. The pattern of impairment is intermediate when compared to groups with schizophrenia and healthy controls.